PENGUKURAN KINERJA BERBASISVALUE FOR MONEY STUDI PADA SMP NEGERI 2 BANJARNEGARA - Sulastiningsih Sulastiningsih; Ida Sulistyowati (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2015)
The purpose of this research is to evaluate the financial performance of SMP Negri 2 Banjarnegara using by the value for money method. Value for money method is an expansion scope from financial audit. Indicators of performance measurement in this research consist of economic, efficiency and effectiveness. The economic performance measurement related to how frugal expenditure was made. The efficiency associated measurement of usefulness budget. The effectiveness relates how to achievement target is appropriate. This research object is managing SMP Negeri 2 Banjarnegara School Budget Plan and School Budget Expenditure realization with based the data on year of 2010/2011. Data collection technique in this research using by interviews and documentation. Based on the analysis concluded that SMP Negeri 2 Banjarnegara yet to implement school-based performance assessment with value for money method. Based on the analysis of school-based performance assessment concluded that the value for money achieved economic level indicates the value of 96.19%, and based on economic criteria tables of financial performance is in less economical criteria. Degree of efficiency showed a value of 100%, based on the value of the efficiency of financial performance criteria is in less efficient criteria. The level of effectiveness showed a value of 96.19%, based on the value of the effectiveness criteria on financial performance criteria is in effective criteria.